Empowerment of a Family Creative Economy through the Utilization of Natural Materials to be a Hand Sanitizer for COVID-19 Prevention: Pemberdayaan Ekonomi Kreatif Keluarga Melalui Pemanfaatan Bahan Alami Menjadi Hand Sanitizer untuk Pencegahan COVID-19 - Wahyu Utami; Karisma Ayu Ningtyas; Vira Safitri; Endang Mawarti; Lilla Puji Lestari (Mattawang: Jurnal Pengabdian Masyarakat, 2021)
The KKNT-KK activity of the Urip Sumoharjo Group purpose to provide public understanding of the importance of 3M in preventing the spread of the corona virus. As well as improving community skills in the use of natural ingredients for the manufacture of hand sanitizers. The method used in this activity is education and socialization of the application of 3M for the prevention of the corona virus, practicing how to make hand sanitizers from natural ingredients. The targets in this KKNT-KK activity are the people of Kalijaten Village, Taman Subdistrict, Sidoarjo Regency, especially mothers. The result of this activity is that the community has begun to understand the importance of 3M, and can utilize natural ingredients for the manufacture of hand sanitizers. Abstrak Kegiatan KKNT-KK Kelompok Urip Sumoharjo ini bertujuan untuk memberikan pemahaman masyarakat tentang pentingnya 3M untuk mencegah penyebaran virus corona. Serta meningkatkan keterampilan masyarakat dalam pemanfaatan bahan alami untuk pembuatan hand sanitizer. Metode yang digunakan pada kegiatan ini adalah edukasi dan sosialisasi penerapan 3M untuk pencegahan virus corona, mempraktekkan cara pembuatan hand sanitizer dari bahan alami. Sasaran dalam kegiatan KKNT-KK ini yaitu masyarakat Kelurahan Kalijaten Kecamatan Taman Kabupaten Sidoarjo khususnya para ibu-ibu. Hasil dari kegiatan ini adalah masyarakat mulai paham tentang pentingnya 3M, serta bisa memanfaatkan bahan alami untuk pembuatan hand sanitizer.